EXPLORING ENGLISH TEACHERS’ SELF-REGULATION TO PROMOTE ONLINE LEARNING IN SENIOR HIGH SCHOOL - R. Indrajid Lukman Santoso; Paulus Kuswandono (Universitas Islam Negeri Alauddin Makassar, 2021)
Rapid changes of current conditions forced English teachers to switch the conventional learning process in a class into online learning. Time zones, internet connection, bandwidth, technical issues, and students’ personal schedules (work vs study) are the challenges faced by the teachers. However, a prior study showed that self-regulation plays a role in online learning. Therefore, teachers’ self-regulation in promoting online learning may lead the way to face those challenges. This study aimed to investigate English teachers’ self-regulation and challenges in promoting online learning. Two research questions were formulated, namely how the self-regulation of English teachers promoted online learning and what challenges were encountered by the English teachers in promoting online learning. To answer these questions, a qualitative approach was undergone. The participants of the study were fourteen (14) English teachers from various areas in Indonesia. The instrument of this study was a questionnaire adapted from Teacher Self-Regulation Scale (TSRS). Findings and results from both questionnaires and interviews suggested that the majority of teachers have fairly high self-regulation as indicated by their good comprehension of goal-setting, emotional control, help-seeking, and self-evaluation. Nevertheless, they found challenges in teaching online classes, namely the lack of students’ internet data and learning motivation, and the need to maintain interactivity and enjoyment in the teaching-learning process. Several strategies were implemented by the teachers to overcome those challenges. Overall, the findings suggest that having adequate self-regulation can lead the teachers to promote online learning in this unprecedented situation. Keywords: Self-regulation, online learning, pandemic situation